Pré-tratamento de bagaço de malte utilizando sistemas de ultrassom para a posterior produção de bioetanol - Silva, Thamires Rafaelle da (2024)
This work investigated the bioethanol production from brewer’s spent grain (BSG) using different ultrasound systems for pretreatment. Ultrasound systems (baths and probes) were evaluated, with frequencies ranging from 20 to 130 kHz and power ranging from 100 to 750 W, using only water as the pretreatment medium. BSG had a cellulose and hemicellulose content of 12.9 ± 1.1% and 18.7 ± 0.6%, as well as a starch content of 10.1 ± 1.3%, which can be converted into fermentable sugars, making it an excellent raw material for biofuel production. The results using X-ray diffraction (XRD) indicated that, in all the evaluated ultrasound systems, the crystallinity of the malt bagasse remained unchanged. However, for the probe operating at 130 W and 20 kHz, a decrease in crystallinity from 58.9 to 48.2% was observed, suggesting that this specific ultrasound condition may have an impact on the crystalline structure of the biomass. As for the morphology observed by scanning electron microscopy (SEM), the malt bagasse without pre-treatment kept its structure intact. In contrast, the samples pretreated with different ultrasound systems showed cracks and cavities, showing the morphological change caused by the ultrasound processes. Among the systems evaluated, the optimized conditions were pretreatment with an ultrasound bath at 130 kHz (200 W/27.2 W dm-3) and pretreatment with an ultrasound probe at 20 kHz (130 W/70.6 W dm-3). After pre-treatment, the best pretreated BSG was selected for enzymatic hydrolysis and subsequent fermentation to produce bioethanol. The kinetics of enzymatic hydrolysis were evaluated for the BSG pretreated using the two ultrasound systems, showing a maximum rate of 3.6 g/100 g h cellulose (200 W/27.2 W dm-3) and 4.2 g/100 g h cellulose (130 W/70.6 W dm-3). For the kinetics of BSG with the 20 kHz probe (130 W/70.6 W dm-3) the rate was higher, correlating with a higher sugar yield, demonstrating the efficiency of this system in pretreating BSG. Among the systems evaluated, the optimized conditions were pre-treatment with an ultrasound bath at 130 kHz (200 W/27.2 W dm-3) and pretreatment with an ultrasound probe at 20 kHz (130 W/70.6 W dm-3). After pretreatment, the best pretreated BSG was selected for enzymatic hydrolysis and subsequent fermentation to produce bioethanol. Pretreatment with the ultrasound probe at 20 kHz (130 W/70.6 W dm-3) resulted in a sugar yield of 46.2 ± 1.5 g/100 g of BSG and an ethanol yield of 1.49%. On the other hand, pretreatment with the ultrasound bath at 130 kHz (200 W/27.2 W dm-3) resulted in a sugar yield of 38.6 ± 0.61 g/100 g of BSG and an ethanol yield of 0.826%. These yields were compared with studies in the literature that used acids (H2SO4, HNO3, among others) with concentrations (ranging from 1 to 4 mol L-1), at temperatures above 100 °C and pressures above 1.5 atm, which resulted in ethanol yields similar to those found in the literature, ranging from 1.2 to 1.4%, using the yeast Saccharomyces cerevisiae. However, it is important to note that the ethanol yield obtained in this study for the 20 kHz ultrasound probe (130 W/70.6 W dm-3) was higher than most of the studies found in the literature, which use diluted acids and more severe conditions for pretreating the biomass. The results of this study demonstrate the effectiveness of ultrasound systems, offering a good yield of ethanol under milder conditions, and showing the viability of ultrasound as a promising alternative for the sustainable production of bioethanol from agro-industrial waste.